Internet and World Wide Web simplified - Wing, Kelleigh (IDG's 3-D visual series, 1999)
Introduces the Internet and the World Wide Web, provides advice on electronic mail, newsgroups, chat, file transfers, Gopher sites, security, and shopping, and lists newsgroups and web sites of interest.